Integrating reflection into a mobile-assisted reading program for learning English as a second language in China - Wang, Fei; Yuizono, Takaya; Wang, Tzu-Yang; Kim, Eunyong; Lu, Yaqin (Frontiers in Education, 2023)
The application of mobile technology in language education is gaining increasing momentum for its potential benefits, and scholars cast attention to issues such as learner motivation, learning effects and learner behaviors in the mobile learning process. Reflection is an essential part in learning as it can record learner behaviors, cultivate self-awareness of knowledge construction, facilitate cognitive growth, and promote academic achievement. Despite of the wide approval of reflection, not much study has been done concerning the application of reflection in mobile language learning process. Therefore, this study aims to investigate students’ perception of a mobile-assisted reading program facilitated with reflective activities as well as their preferences for reflection modes adopted. The participants were 60 students from two classes in a Chinese college. Students read passages on mobile applications and completed a reflection in one mode every two weeks. Four modes (paper journal reflection, e-journal reflection, audio reflection, and collaborative reflection) were adopted in the study. The study lasted approximately nine weeks. At the end of the program, all students were required to complete an anonymous questionnaire concerning their learning perception. In addition, ten students were selected randomly to attend a semi-structured interview. A pretest and a posttest were conducted to observe students’ language gains. A combination of quantitative and qualitative analysis was conducted with the data obtained. Results showed students generally approved of the effect of this mobile-assisted reading and their reading proficiency improved significantly after the program. In addition, most students favored reflective practices as a good way to stimulate interest, deepen understanding and promote reflective and summarizing abilities, but they didn’t consider it a good method to monitor the learning process in the mobile-assisted reading program. As for the preference for reflection mode, most students favored traditional paper reflection and audio reflection, while collaborative reflection and e-journal reflection received the least support. The findings provided implications for educators and app designers. For educators, based on the understanding of students’ age, learning experience, and possible preferences, they may create a good reflective environment with technical and instructional support, and then provide two or three popular modes for students to reflect on whatever they read. For app developers, some preferable reflection modes facilitated with stimulative measures may be offered to cater to more learners to conduct reflective activities.